Large-Scale Formation of DNA Origami Lattices on Silicon - Tapio, Kosti; Kielar, Charlotte; Parikka, Johannes M.; Keller, Adrian; Järvinen, Heini; Fahmy, Karim; Toppari, J. Jussi (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Single-Layer T′ Nickelates: Synthesis of the La and Pr Members and Electronic Properties across the Rare-Earth Series - Wissel, Kerstin; Bernardini, Fabio; Oh, Heesu; Vasala, Sami; Schoch, Roland; Blaschkowski, Björn; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver; Cano, Andrés (Chemistry of Materials)
Understanding high-temperature unconventional superconductivity has become a long-lasting problem in which the cuprates stand as central reference materials. Given this impasse, the recent discovery of superconductivity in analogous nickelate thin films represents a fundamental breakthrough calling for the identification of additional materials in this class. In particular, thermodynamically more robust systems are required to “upgrade” nickelate superconductors from thin films to bulk samples. Here, we contribute in this direction by reporting the synthesis of the new single-layer T′ Pr2NiO3F compound, assessing this synthesis in relation to the only previous T′ nickelate La2NiO3F, and analyzing the electronic properties across the R2NiO3F series (R = La–Lu) via first-principles calculations. We find that these mixed anion systems have a comparatively high degree of stability and their synthesis enables a fine-tuning of their composition as inferred from their characterization. Furthermore, we find that these unprecedented square-planar nickelates hold great promise as prospective superconductors due to their exceptional electronic structure.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Quantification of Efficiency in Lithium Metal Negative Electrodes via Operando X-ray Diffraction - Geise, Natalie R.; Kasse, Robert M.; Nelson Weker, Johanna; Steinrück, Hans-Georg; Toney, Michael F. (Chemistry of Materials)

Toward Unraveling the Origin of Lithium Fluoride in the Solid Electrolyte Interphase - Cao, Chuntian; Pollard, Travis P.; Borodin, Oleg; Mars, Julian E.; Tsao, Yuchi; Lukatskaya, Maria R.; Kasse, Robert M.; Schroeder, Marshall A.; Xu, Kang; Toney, Michael F.; Steinrück, Hans-Georg (Chemistry of Materials)

Electrochemical Reduction and Oxidation of Ruddlesden–Popper-Type La2NiO3F2 within Fluoride-Ion Batteries - Wissel, Kerstin; Schoch, Roland; Vogel, Tobias; Donzelli, Manuel; Matveeva, Galina; Kolb, Ute; Bauer, Matthias; Slater, Peter R.; Clemens, Oliver (Chemistry of Materials)
Within this article, it is shown that an electrochemical defluorination and additional fluorination of Ruddlesden–Popper-type La2NiO3F2 is possible within all-solid-state fluoride-ion batteries. Structural changes within the reduced and oxidized phases have been examined by X-ray diffraction studies at different states of charging and discharging. The synthesis of the oxidized phase La2NiO3F2+x proved to be successful by structural analysis using both X-ray powder diffraction and automated electron diffraction tomography techniques. The structural reversibility on re-fluorinating and re-defluorinating is also demonstrated. Moreover, the influence of different sequences of consecutive reduction and oxidation steps on the formed phases has been investigated. The observed structural changes have been compared to changes in phases obtained via other topochemical modification approaches such as hydride-based reduction and oxidative fluorination using F2 gas, highlighting the potential of such electrochemical reactions as alternative synthesis routes. Furthermore, the electrochemical routes represent safe and controllable synthesis approaches for novel phases, which cannot be synthesized via other topochemical methods. Additionally, side reactions, occurring alongside the desired electrochemical reactions, have been addressed and the cycling performance has been studied.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Morphology of Organic Semiconductors Electrically Doped from Solution Using Phosphomolybdic Acid - Huang, Tzu-Yen; Larrain, Felipe A.; Borca, Carlos H.; Fuentes-Hernandez, Canek; Yan, Hongping; Schneider, Sebastian Alexander; Chou, Wen-Fang; Rodriguez-Toro, Victor A.; Steinrück, Hans-Georg; Cao, Chuntian; Sherrill, C. David; Kippelen, Bernard; et al. (Chemistry of Materials)

Synthesis and Characterization of Vanadium-Doped LiMnPO4-Compounds: LiMn(PO4)x(VO4)1–x (0.8 ≤ x ≤ 1.0) - Clemens, Oliver; Bauer, Matthias; Haberkorn, Robert; Springborg, Michael; Beck, Horst Philipp (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Evaluation of Homoleptic Guanidinate and Amidinate Complexes of Gadolinium and Dysprosium for MOCVD of Rare-Earth Nitride Thin Films - Thiede, Tobias B.; Krasnopolski, Michael; Milanov, Andrian P.; de los Arcos de Pedro, Maria Teresa; Ney, Andreas; Becker, Hans-Werner; Rogalla, Detlef; Winter, Jörg; Devi, Anjana; Fischer, Roland A. (Chemistry of Materials)

Controlling Zeolitic Imidazolate Framework Nano- and Microcrystal Formation: Insight into Crystal Growth by Time-Resolved In Situ Static Light Scattering - Cravillon, Janosch; Nayuk, Roman; Springer, Sergej; Feldhoff, Armin; Huber, Klaus; Wiebcke, Michael (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Rapid Room-Temperature Synthesis and Characterization of Nanocrystals of a Prototypical Zeolitic Imidazolate Framework - Cravillon, Janosch; Münzer, Simon; Lohmeier, Sven-Jare; Feldhoff, Armin; Huber, Klaus; Wiebcke, Michael (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry